Degree of peer pressure and its influence on real estate management students financial goals and behaviors: Applications for financial literacy program in the academe - Ciego, Ailheenel Keynt A., Fojas, Joana Marie B., Gadaiza, Maria Anjela M., Matias, Maria Victoria C., Pacheco, Pauline Grace P., Santos, Cresta Fe Coleen J. 4 0 16; 5 (2023)
Abstract This study entitled, Degree of peer pressure and its influence on Real Estate Management students' financial goals and behaviors: Applications for financial literacy program in the academe was prepared by Ailheenel Keynt A. Ciego, Cresta Fe Coleen J. Santos, Joana Marie B. Fojas, Maria Anjela M. Gadiaza, Maria Victoria C. Matias, and Pauline Grace P. Pacheco in partial fulfillment of the requirements for the subject Business Research. This was prepared under the supervision of Dr. Marivic F. Flores. The main objective of the study is to assess the degree of influence of peer pressure on Real Estate Management students financial decision-making process including their financial goals and behaviors in terms of earning, saving, investing, and spending. The study aims to provide practices which are beneficial to the academe on the development of the financial literacy programs. The study sought to address the demographic profile of the respondents, determine how the following aforementioned factors influence the financial goals and behaviors of business students, moreover, investigate whether there is a significant difference between the degree of influence of peer pressure on respondents' financial goals and behaviors in terms of earning, saving, investing, and spending when group according to their profile. The researchers used the descriptive approach in this study. There were 177 respondents coming from the Real Estate Management of Pamantasan ng Lungsod ng Maynila who were chosen using census. A survey questionnaire was employed to gather necessary information. The statistical tools used by the researchers were Frequency Distribution, Percentage Distribution, Ranking, Weighted Mean, ANOVA, and Likert Scale. Based on the findings, it was discovered that Real Estate Management students in Pamantasan ng Lungsod ng Maynila is highly influenced by their peers in terms of earning, saving and spending which means that there is a high degree of peer pressure on building their financial goals and behaviors thus peers play a significant role on decision making processes of the Real Estate Management students. On the other hand, investing shows to be not that influential hence this may be supported by the fact that students prioritize more on other aspects of financial goals such us the earning, saving and spending compared to investing. Based on the study's findings, the researchers recommend that academe should have an additional subject provided from other course known as Investment Analysis and Portfolio Management (IPM), which is not included in the REM's curriculum. This highlights investments on other assets particularly stocks, bonds, mutual funds, and diversification strategies of securities that could help promote an effective investment management skills. In addition, the said program has a qualified professionals that would play a significant role in guiding and educating students to make well-informed investment decisions. The researchers also recommend that parental and school influences could be considered on factors influencing the students financial goals and behaviors. Lastly, future researchers should include more schools on future studies and add more factors in the financial goals and behavior of college students.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2